Comparative analysis on metallography, hardness, and corrosion rate of repair methods in welding tube SA-213 to tubesheet SA-240 - Moh. Syaiful Amri; Alvalo Toto Wibowo; Muh. Ofirsyah Apriliano Ananda Dzikrilla (Journal of Welding Technology, 2025)
In the fabrication process of heat exchangers, tube-to-tubesheet weld joints are often prone to defects such as porosity, cracking, undercut, and other forms of damage that can degrade the quality and performance of the equipment. To address these issues, repair becomes a crucial solution. However, due to the lack of standardized repair procedures, alternative methods such as TIG dressing and flush and reweld using filler metals of various diameters are commonly applied for the sake of time and cost efficiency. This study aims to compare three repair methods TIG dressing, flush and reweld using diameters 1.6 mm filler, and diameters 2 mm filler on macrostructure, microstructure, hardness, and corrosion rate of tube-to-tubesheet weld joints. The tests conducted include macro and micro examinations, Vickers Hardness testing, and corrosion rate. The results showed that Repair 1 (TIG dressing) produced a finer ferrite phase in the weld metal area and achieved the highest average Hardness value of 234.4 kgf/mmÂ², although it also exhibited the highest corrosion rate at 0.44053 mm/year. In contrast, Repair 2 showed the lowest Hardness in the weld metal area, with an average of 221.9 kgf/mmÂ², and the lowest corrosion rate of 0.28036 mm/year. Therefore, the TIG dressing method proves to be more effective in improving Hardness, but at the expense of an increased corrosion rate